An assessment of the livestock by-products value chains in Somaliland: The case of bones and tallow - Mtimet, Nadhem; Mugunieri, Lawrence Godiah; Wanyoike, Francis N.; Kiptoo, Enock; Gulaid, Ibrahim (Springer, 2018)
Livestock and livestock product exports are the main source of foreign currency earning in Somaliland. However, in the recent past, the growth in earnings from livestock sales has been declining against a background of increasing human population growth. Adding value to the livestock and livestock products provides an avenue for reversing the declining growth in incomes. This report presents the findings of a study that assessed the bone and tallow value chains in Somaliland. The assessment mapped and characterised these value chains and also identified the main constraints that hinder their development. The results showed that both value chains are short, use low-value inputs, produce relatively low-valued products and involve participants from minority groups, women and youths. This implies that they offer an opportunity for inclusive economic growth that encompasses the most vulnerable groups in the country. The final product in the tallow value chain is laundry soap, while bone trinkets are crafted from camel bones. Besides, the two value chains are complementary, such that some of the fats used to make soap are obtained from bone marrow fats, with the bones used in crafting of ornamental products. However, the two value chains have failed to exploit the various opportunities for growth due to a number of constraints that include low quality of the final products, lack of access to working and investment capital and inconsistent supply of raw materials. Strengthening of these promising value chains will require the following interventions among others : (i) improvement of the processing skills of the value chain actors through appropriate trainings to allow the development of quality products; (ii) enhancing access to working and investment capital, through the financial institutions or donors, that will allow acquisition of the necessary new equipment to upgrade the quality and quantity of the products; and (iii) review and/or develop new business plans for the existing businesses that should include, among others, a clear sustainable growth strategy and vision.